(untitled) (Advancements in Homeopathic Research, 2023)
Background: Alopecia areata is a form of alopecia that affects hair follicles. It presents with round patch. Many treatments are available and this review highlights the usage of homoeopathy in treatment of alopecia areata. Objective: The review was done to explore the strengths of homoeopathy in management of alopecia areata through online available evidences. Methods: A search was made for homoeopathic management of Alopecia areata in PubMed, AYUSH Research Portal, Google Scholar, Google search engines was done to collect all relevant articles, reports, web pages published till October 2022. The term included was Alopecia homoeopathic treatment, Alopecia homoeopathy, Alopecia areata homoeopathy. Further literature review was also conducted & repertory was also searched. Result: 16 studies were found and all are case reports except one. Conclusion: At present available evidences for homoeopathic management of alopecia are very weak. Further studies are needed for strong evidences.